(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India is the thirdlargest mobile network in the world after China and USA. Indian mobile marketis one of the fastest growing markets. India has seen rapid increase in thenumber of players which caused the tariff rates to hit an all time low. Thisallowed the players to target the low income population thereby increasing themarket share. The availability of a number of subscriber options for consumersand varied tariff rates of each player, lead the consumers to switch betweenservice providers. The objectives of the study are to find the factors thatinfluence the consumers in switching the service provider and to delve intofinding out the likeliness of switching the service provider. Factorsinfluencing the switching behaviour and factors that affect the switchingbehaviour of consumers and these were grouped into 4 categories namely customerservice, service problems, usage cost and others. The results from the studyreveal that call rates plays the most important role in switching the serviceprovider followed by network coverage, value added service and customer carewhile advertisement plays the least important role. It is found that there is arelation between switching the service provider and the factors (customerservice, service problem, usage cost, etc.). After analysing the findings ofthe study, we propose that the mobile providers concentrate on increasingnetwork stability and setting tariff rates competitively. The expanding Indianeconomy, the population with younger people, the urbanization with increasedincome of the household and the like provide vast scope in the cellular servicemarket. At the same time, as competition in the telecom is intensified, serviceproviders take new initiatives to attract customers as the requirements andexpectations of the customer are increasing very fast. There is also anincrease in the expectations of the product and service in terms of confirmingto certain standards, reliability, dependability, durability, performance,features, appearance, safety and user-friendliness. Though the Cellularoperators have been rendering services to the customers throughout India, thereis dissatisfaction expressed by the customers over excess billing,disconnection while talking, cross talk, high cost of handsets and highoperating cost. Due to these factors the cellular operators have come under alot of strong criticism. In this Article, the aspects relating to switchingtendencies of consumers of mobile phone services are studied.